Seed diversity in the Miconieae (Melastomataceae): morphological characterization and phenetic relationships - Ocampo, Gilberto; Almeda, Frank (Phytotaxa, 2013)
The seed morphology of 234 species distributed among 16 genera of the tribe Miconieae (Melastomataceae) was examined and documented with the use of scanning electron microscopy (SEM). Based on our observations and previously published investigations, we propose a set of 37 morphological characters for describing size, general shape, raphal zone, appendage, testa characters, and individual cell features of Miconieae seeds. Using these characters, we assembled detailed descriptions of all species in our sampling and constructed a data matrix for preliminary phenetic analysis (UPGMA algorithm; results to be presented elsewhere). In general, seed characters were easily identified and coded, although some of them presented difficulties, mostly due to the compression effects induced by fruit walls and neighboring seeds (e.g., shape). In contrast with other studies, we avoided the use of morphotypes, which have been shown to underutilize phenotypic variation. Our phenetic analysis does not agree with the traditional generic circumscription of the tribe, the sectional classification within Miconia, or with molecular phylogenetic analyses. This raises questions about the systematic and phylogenetic value of seed morphological characters in the tribe Miconieae.